Capability exposure deployment of IMS core network - Wei QIU; Qian WU; Hai WU (Dianxin kexue)
Based on existing communication network capacity,telecom operators build the capability exposure platform,third-party developers were attracted to develop more colorful personalized communication services to users,new opportunities and challenges was brought to telecom operators.The construction plan and capability exposure pattern of system architecture of capability exposure and IMS network capability platform was analyzed,references of actual deployment for capability exposure were provided.